The Effect Pengaruh Mengkonsumsi Sari Kurma dan Buah Naga dengan Peningkatan Kadar Hemoglobin untuk Pencegahan Anemia - Liss Dyah Dewi Arini; Nabulatul Fanny; Devi Pramita Sari (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
The World Health Organization (WHO) stipulates that anemia criteria use hemoglobin levels, namely in women under 12 g / dL and in men less than 13 g / dL. Anemia level someone is influenced by the food they consume, where a person consumes foods that have a low Fe content will occur anemia. Hemoglobin is part of the blood which has an important role in forming red blood cells. Iron is needed in the process of blood formation. Copper substances contained in palm juice are needed by the body to form red blood cells. Red blood cell production is small, red blood cell damage and blood loss can cause a person suffering from anemia. Sari dates and dragon fruit are rich in iron which is useful for forming red blood cells. The purpose of this study was to determine the effect of dates palm juice and dragon fruit in increasing hemoglobin levels. The population in this study is the same as the sample, namely 40 female workers at the Surakarta Gelora convection, which were divided into two groups: 20 people (group 1) who were given palm juice and 20 people (group 2) were given dragon fruit. The tool used in this study is a measure of hemoglobin levels in the blood, check list. The conclusions of this study were the average pre-test hemoglobin levels by giving palm juice of 10.61 and the post-test average hemoglobin level of 11.53 and the average hemoglobin level before and after being given dragon fruit by 10.42 and the average average post-test hemoglobin level of 10.62.